Study on the role of tissue-specific and non-specific autoantibodies, matrix metalloproteinase-3 and neuron-specific enolase enzymes in the exacerbation of autoimmune thyroiditis - R. R. Rahimova; A. M. Efendiyev; I. J. Shahverdiyeva; G. S. Dashdamirova; S. R. Guliyeva; U. H. Azizova (Zaporožskij Medicinskij Žurnal)
The aim of the study was to examine the involvement of tissue-specific and non-specific autoantibodies, matrix metalloproteinase-3 and neuron-specific enolase (NSE) enzymes in the development and exacerbation of autoimmune thyroiditis.